2011
DOI: 10.1016/j.otsr.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Component impingement in total hip arthroplasty: Frequency and risk factors. A continuous retrieval analysis series of 416 cup

Abstract: Component impingement is frequently observed in cups after removal, but is rarely found as a direct indication for revision, except in case of hard-on-hard friction couples (polyethylene being the most impingement-tolerant material). Systematic use of extended head flanges and elevated antidislocation rims is not to be recommended, especially in case of excessive ROM. A good head/neck ratio should be sought, notably by increasing the head diameter in less impingement-tolerant hard-on-hard friction couples. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
5
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 31 publications
5
43
5
3
Order By: Relevance
“…Likewise, revisions because of impingement were done independent of the bearing diameter, suggesting that use of 36-mm CoC bearings does not prevent impingement. This finding is different than the ones from a retrieval study that found the head-neck ratio to affect the occurrence of impingement [24]. However, we have no data on the cup position or head-neck ratio in our study; this may explain the absence of a bearing diameter effect.…”
Section: Discussioncontrasting
confidence: 99%
“…Likewise, revisions because of impingement were done independent of the bearing diameter, suggesting that use of 36-mm CoC bearings does not prevent impingement. This finding is different than the ones from a retrieval study that found the head-neck ratio to affect the occurrence of impingement [24]. However, we have no data on the cup position or head-neck ratio in our study; this may explain the absence of a bearing diameter effect.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, Marchetti et al [97] found no correlation between impingement and cup position in a retrieval study. In conclusion, impingement seems to be a common problem with THR and should be considered during wear tests, although not at every load cycle.…”
Section: Impingement Testingmentioning
confidence: 89%
“…Morphologic risk factors for prosthetic dislocation are well known, including decreased femoral head-neck offset [1,10], decreased femoral antetorsion [8], and retroversion of the acetabular cup [9,16]. In contrast, there is limited information regarding the etiology of traumatic hip dislocations of the native hip.…”
Section: Introductionmentioning
confidence: 99%